Peran Psikologi Olahraga dalam Pembelajaran PJOK terhadap Motivasi dan Mental Siswa - Munugara, I Made Era Junva; Lesmana, Kadek Yogi Parta; Semarayasa, I Ketut; Danardani, Wasti (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
This study aims to describe the implementation of sport psychology principles in Physical Education, Sport, and Health (PJOK) activities at SMA Negeri 2 Amlapura and to analyze their impact on students’ motivation and mental resilience. Data were collected through observation, in-depth interviews, and documentation using research instruments in the form of structured observation sheets containing indicators of intrinsic motivation, positive reinforcement, and emotional regulation; semi-structured interview guidelines consisting of open-ended questions for teachers and students; and documentation formats including field notes, recordings of learning activities, and instructional documents such as teaching modules. The data were analyzed using triangulation techniques to ensure data validity. The results show that PJOK teachers have applied sport psychology principles contextually through intrinsic motivation enhancement, positive reinforcement, and self-reflection activities. This implementation effectively increased students’ learning enthusiasm, self-confidence, and emotional control. Moreover, the psychological approach in PJOK created a positive and inclusive learning environment that supports students’ mental well-being. However, several challenges remain, including limited sports facilities, lack of formal psychological support, and varying student abilities. Overall, the findings emphasize that applying sport psychology principles significantly contributes to character formation, motivation, and mental health development in physical education learning.